2012
DOI: 10.1115/1.4007487
|View full text |Cite
|
Sign up to set email alerts
|

Error Modeling and Experimental Validation of a Planar 3-PPR Parallel Manipulator With Joint Clearances

Abstract: This paper deals with the error modeling and analysis of a 3-PPR planar parallel manipulator with joint clearances. The kinematics and the Cartesian workspace of the manipulator are analyzed. An error model is established with considerations of both configuration errors and joint clearances. Using this model, the upper bounds and distributions of the pose errors for this manipulator are established. The results are compared with experimental measurements and show the effectiveness of the error prediction model. Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 39 publications
(19 citation statements)
references
References 19 publications
0
19
0
Order By: Relevance
“…The deflection of the robot was measured via an experimental setup composed of a single Charge-Coupled Device (CCD) camera with an interface 18 :…”
Section: Experimental Verification Of the Stiffness Modelmentioning
confidence: 99%
“…The deflection of the robot was measured via an experimental setup composed of a single Charge-Coupled Device (CCD) camera with an interface 18 :…”
Section: Experimental Verification Of the Stiffness Modelmentioning
confidence: 99%
“…Few of the commercially available and research planar parallel robotic platforms along with the proposed manipulator are presented in Fig.1. A small number of research works have been carried out based on the 3-PPR configuration and reported in the literature [48][49][50][51][52][53]. However, these works are limited to kinematic analysis, error analysis, stiffness analysis and mechanical optimum design aspects of the manipulator.…”
Section: Introductionmentioning
confidence: 99%
“…Thereafter, a sample value of the terminal Δp can be obtained by the matrix in equation (12). The frequency distribution histogram can be obtained on the basis of the multiple sampling values.…”
Section: Reliability Analysis Of Static Position Errormentioning
confidence: 99%
“…According to equation (12), the position errors of the robot in the given reference point also obey the normal distribution in every direction: x, y, z, and the final error direction. The mean and variance can be approximately obtained by the moment method and can be expressed as follows: The final position errors of the position error can be expressed as follows:…”
Section: Reliability Analysis Of Kinematic Accuracymentioning
confidence: 99%
See 1 more Smart Citation